Digitalizing bullying: do Nigerian students get cyberbullied? - Atanda, Balogun Naeem; Ahlan, Abdul Rahman; Awodele, Taofeekat Adedolapo (Institute of Electrical and Electronics Engineers Inc., 2018)
This study aims to assess the relationship that exists between the frequent usage of social networks and the practice of cyberbullying among Nigerian University students, also the level of their understanding on bully in the digital world. The study used questionnaire-based survey to gather responses from these universities students to understand their usage of social networks and also their experience with cyberbullying. Findings of this study show significant relationship between the frequent use of social networks and the practice of cyberbullying. The context of this study is limited to universities within Ilorin Emirate Council of Kwara State in Nigeria which comprise of three universities. Findings of the study show students understanding of how to avoid cyberbullying on social networks. The research provides useful information for universities students on how to better use social networks and guard against getting bullied on social networks.